THE EFFECT OF RELIGIOSITY AND BOYCOTT DECISIONS ON BRAND LOYALTY OF PRO-ISRAEL PRODUCTS - Sugeng Nugroho Hadi; Khadijah Syafira Adyani (Jurnal Ilmu Manajemen (JIMMU), 2025)
AbstractThe boycott action against pro-Israel products is widely voiced by Muslim consumers as a form of concern for Muslims in Gaza, Palestine, who have been unjustly massacred for years, triggering genocide by the Israeli Zionists. This study aims to determine the influence of religiosity and brand loyalty on the action of Muslim boycott decisions against pro-Israel products. From this objective, a research question can be developed, "Does the religiosity and brand loyalty of Muslims affect the decision to boycott pro-Israel products?" With the hope that the decision to boycott pro-Israel product loyalty will have an effect on business (economic) losses for Israel and its allies. This study is a quantitative study with an associative descriptive approach. The sample design used 100 respondents, namely Muslim consumers who have or frequently use pro-Israel products. The sampling technique used is non-probabilty purposive sampling. Data analysis uses multiple linear regression. The results of the study answer the research questions that partially, (i) Religiosity has a significant effect on the decision to boycott; and (ii) Brand Loyalty also has a significant effect on the decision to boycott. Meanwhile, simultaneously, (iii) Religiosity and Brand Loyalty have a significant influence on the decision to boycott pro-Israel products. The multiple regression model is shown by the equation Y = 16.854 + 0.207X1 + 0.248X2 with a determination of 27.7%. This means that the high value of boycotting pro-Israel products indicates that this movement or action is seen as effective for fanatical Muslims. However, the number of Muslims who are less or not fanatical about their beliefs (Islam) is still quite large. So it can be stated that the boycott action is only effective for or when Muslims are fanatical about their teachings (Islam).